Seabed Mineral Resources and the Economic Interests of Developing Countries - Leipziger, Danny M.; Mudge, James L. (Cambridge, Massachsetts : Ballinger Publishing Company, 1976)
In recent years, the literature on seabed mineral resources has largely focused on legal, political, and technical aspects. The few economic treatments have tended to be relatively restricted. One of the main purposes of this undertaking is to make a first attempt at providing a reasonably comprehensive and systematic examination of the major economic issues related to allocation and production of the virtually untapped stock of seabed hydrocarbons and manganese nodules. This study also pursues another objective, which is to attempt to contribute to the body of economic information for use by countries in their international negotiations on seabed resource issues.
Includes index.
Bibliography: p. 225-234.
ne 16/04/2018
Loans
Keywords: Mineral Industries; Mineral Resources in Submerged Lands; Developing Countries